Thermal modeling and characterization for power devices (IGBT) - Sulaiman Mohamed. (2011)
Temperature junction constraints in power semiconductor devices are one of the factors that can determine whether it would change in its operation or go into failure. It is thus essential to create models and characterization techniques to determine this effect of junction temperature on the power semiconductor devices. In this report, there is a need to understand how a simple power device works. The characteristics of the power device are also observed. The power semiconductor device that will be used is an IGBT. For the experimentation process, Simplorer will be used to analyze and provide simulation results to determine the IGBT junction temperature. Other than the simulation, a practical experimentation will also be done. Results from both the simulation and practical experimentation will be compared to create the general thermal characteristic of the IGBT module.